2016
DOI: 10.1002/ijc.30003
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant splicing of the DMP1ARFMDM2‐p53 pathway in cancer

Abstract: Alternative splicing of mRNA precursors is a ubiquitous mechanism for generating numerous transcripts with different activities from one genomic locus in mammalian cells. The gene products from a single locus can thus have similar, dominant-negative, or even opposing functions. Aberrant alternative splicing has been found in cancer to express proteins that promote cell growth, local invasion, and metastasis. This review will focus on the aberrant splicing of tumor suppressor/oncogenes that belong to the DMP1-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 87 publications
(252 reference statements)
0
41
0
Order By: Relevance
“…These observations suggested an oncogenic role of ETS1 in breast tumorigenesis (87). In contrast to ETS1 , loss of the Myb-like transcription factor DMP1α ( DMTF1α ) binds to the Ets site in the Arf promoter (91) is associated with low Ki67 and is associated with favorable prognosis (92) for Dmp1 original articles; 93101; 67, 102106 for reviews). Dmp1α also binds directly to p53 for activation in Arf -deficient cells (100, 101).…”
Section: Ets1 and Ets2mentioning
confidence: 99%
“…These observations suggested an oncogenic role of ETS1 in breast tumorigenesis (87). In contrast to ETS1 , loss of the Myb-like transcription factor DMP1α ( DMTF1α ) binds to the Ets site in the Arf promoter (91) is associated with low Ki67 and is associated with favorable prognosis (92) for Dmp1 original articles; 93101; 67, 102106 for reviews). Dmp1α also binds directly to p53 for activation in Arf -deficient cells (100, 101).…”
Section: Ets1 and Ets2mentioning
confidence: 99%
“…Our study shows that DMP1β does not bind to p53 (data not shown); whether or not DMP1γ binds to p53 has not been studied. It is very likely that they DMP1γ does not affect the function of p53 because i) it lacks the 2 nd and 3 rd Myb-like domain required for the physical interaction with p53 (52), and ii) DMP1β accelerated the proliferation breast cancer cells independent of p53 (51). To date 40 splice variants have been reported from the hDMP1 locus (89), but only two of them -aAug10 (hDMP1α) and bAUG10 (a variant that lacks the amino-terminal 88 amino acids) encode proteins that can bind to p53.…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported that Dmp1 physically interacts with p53 to neutralize the known functions of Mdm2 (or HDM2), namely ubiquitination, nuclear-cytoplasmic transport, and suppression of transport (47), a very unique property among p53/Mdm2-binding transcription factors (48). The h DMP1 locus encodes at least three splicing variants -h DMP1α, β, and γ with antagonizing functions (4951, reviewed in 52). The h DMP1α gene corresponds to murine Dmp1α that positively regulates the p19 Arf -p53 pathway (761 amino acids [a.a.] in mice, 760 a.a. in humans).…”
Section: Introductionmentioning
confidence: 99%
“…Thus deregulation of HER2 leads to tumorigenesis. Aberrant overexpression of HER2 activates the Dmp1 promoter to stimulate the Arf-Mdm2-p53 self-autonomous tumor surveillance pathway through Pi3k-Akt-NF-κB and Ras-Raf-Mek-Erk-Jun cascades to eliminate incipient cancer cells by cell cycle arrest or apoptosis [10, 15, 57, 63]. …”
Section: Figurementioning
confidence: 99%